Puzzle of highly virulent Metarhizium anisopliae strains from Annona squamosa fields against Helicoverpa armigera - Pathan, Ejaj K.; Deshpande, Mukund V. (Journal of Basic Microbiology, 2019)
In our search for indigenous virulent strains of the entomopathogenic fungi, we observed that Metarhizium isolates from soils associated with Annona squamosa (custard apple) have higher virulence (>90% mortality of Helicoverpa armigera larvae at 1/10(th) spore concentration) than strains isolated from Solanum lycopersicum (tomato) fields. Proteomic analysis revealed two insecticidal cyclopeptides of A. squamosa origin in the M. anisopliae strains that led to higher virulence against H. armigera. Transcriptomic and genomic data indicated that M. anisopliae strains and A. squamosa had more than 20 genes in common, including those for cyclic hexapeptide synthase, non-ribosomal peptide synthetase, and plant cyclotide genes, which are involved in the biosynthesis of insecticidal cyclopeptides. These genes were absent in M. anisopliae strains isolated from the S. lycopersicum fields. Further, these strains can establish an endophytic relationship with A. squamosa suggesting that these rhizospheric strains originally could be endophytes, which were eventually released into the soil. Further, Metarhizium strains associated with Capsicum annuum (chili), Azadirachta indica (neem), and Carica papaya (papaya) - plants with insecticidal properties - also had higher virulence against H. armigera. Thus exploration of rhizospheres of plants producing insecticidal metabolites to isolate entomopathogenic fungi, per se, could be a viable strategy in agricultural for crop protection.
Keywords: Annona squamosa; Biocontrol; endophyte; entomopathogen; Helicoverpa armigera; horizontal gene transfer; insecticidal peptides; Metarhizium; natural transformation